Deteksi Gerakan Kepala Berdasarkan Analisis Bounding Box Pada Citra Digital Berbasis Raspberry Pi - Muzammilatul Jamiilah; Fitri Utaminingrum; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In general, navigation is done by using the hands and feet. However, as we know in Indonesia there are some people who have limitations or do not have hands and feet. So that users who have disabilities in their hands and feet will have difficulty for navigating or controlling the tools. Therefore, this study proposes that head movement as a control can replace the function of hands and feet by utilizing bounding box analysis. This study uses a Logitech C310 camera. The process used in this research is image processing. The output generated in this system is LED Control. Test accuracy results on good skin color detection to detect the face skin color is a distance of 50 cm, 75 cm, 100 cm, and 125 cm at morning and afternoon and also a distance of 50 cm, 75 cm at night. The accuracy of the results of testing the detection of head movement distance and the best time for doing it is at a distance of 50 cm in the morning, afternoon and night with an overall percentage of 90.62%. The average computation time of each movement for the right side is 59.87 ms, the left side is 57.64 ms, upright is 55.72ms, and the last look down is 44.62ms.The accuracy of system integration with hardware or LED is 100%.